2016
DOI: 10.1371/journal.pone.0159175
|View full text |Cite
|
Sign up to set email alerts
|

The AGE-RAGE Axis and Its Relationship to Markers of Cardiovascular Disease in Newly Diagnosed Diabetic Patients

Abstract: AimThe purpose of the study was the simultaneous measurement of all the different components of the AGE-RAGE axis as well as several non-invasive markers of cardiovascular disease (CVD) in a cohort of newly diagnosed diabetic patients.Materials and MethodsIn 80 newly diagnosed diabetic patients we measured serum carboxymethyllysine (CML), soluble RAGE (sRAGE) and peripheral mononuclear (PMNC) RAGE and AGER1 mRNA together with ICAM-1, VCAM-1, and malondialdehyde (MDA). We also assessed cardiovascular function b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…Of interest, serum CML levels in the current cohort were significantly higher than those of obese male adults in another study who had an average age of 43 years (p < 0.001) . They were also only slightly lower than patients newly diagnosed with diabetes, reported by our group, who had an average age of 48.5 years (p < 0.036) . That study used the same methodology for measuring CML as this study and comprised participants of the same region and country.…”
Section: Discussionmentioning
confidence: 42%
“…Of interest, serum CML levels in the current cohort were significantly higher than those of obese male adults in another study who had an average age of 43 years (p < 0.001) . They were also only slightly lower than patients newly diagnosed with diabetes, reported by our group, who had an average age of 48.5 years (p < 0.036) . That study used the same methodology for measuring CML as this study and comprised participants of the same region and country.…”
Section: Discussionmentioning
confidence: 42%
“…Lately, some studies on chronic kidney disease (CKD) patients that were undergoing dialysis revealed that sRAGE was not related to CVD [ 24 , 48 ]. However, Villegas-Rodríguez et al (2016) found a significant association between the AGE–RAGE axis markers, especially the sRAGE, with several non-invasive markers of cardiovascular-disease risk in the population of patients with newly diagnosed diabetes type 2 [ 49 ]. It was also suggested that sRAGE could be a biomarker for a RAGE-mediated disease, especially vascular-disease [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those involved in the endocytosis, breakdown, and removal of AGEs from the circulation; and those that activate a pro-inflammatory cellular response. AGER1, the prototype for the former class, has an additional role in inhibiting the production of reactive oxygen species and cellular defense mechanisms (Lu et al, 2004 ; Villegas-Rodriguez et al, 2016 ; Vlassara & Striker, 2011 ). AGER1 expression is upregulated on acute exposure to increased AGE concentrations, but is suppressed with chronic exposure to oxidative stress and high extracellular AGE levels, consistent with the finding of reduced AGER1 levels in patients with diabetes and chronic inflammatory disease (Vlassara & Uribarri, 2014 ).…”
Section: Main Textmentioning
confidence: 99%